Is maize B chromosome preferential fertilization controlled by a single gene? - Chiavarino, Amílcar Mauricio (2001)
In previous work, genotypes for high and low B chromosome transmission rate were selected from a native race of maize. It was demonstrated that the B transmission is genetically controlled. The present work reports the fourth and fifth generations of selection and the F1 hybrids between the lines. The native B is characterized by a constant behaviour, with normal meiosis and nondisjunction in 100% of postmeiotic mitosis. It is concluded that genetic variation for B transmission between the selected lines is due to the preferential fertilization process. The F1 hybrids show intermediate B transmission rate between the lines. They are uniform, the variance of the selected character being one order of magnitude lower than that of the native population. In addition, 0B×2B and 2B×2B crosses were made to study the effect of the presence of B chromosomes in the female parent, resulting in non-significant differences. Several crosses were made both in Buenos Aires and in Madrid to compare the possible environmental effect, but significant differences were not found. Our results are consistent with the hypothesis of a single major gene controlling B transmission rate in maize, which acts in the egg cell at the haploid level during fertilization. It is also hypothesized that maize Bs use the normal maize fertilization process to promote their own transmission.